2012
DOI: 10.1080/00049182.2012.731300
|View full text |Cite
|
Sign up to set email alerts
|

‘How dare you say that about my friend’: negotiating disability and identity within Australian high schools

Abstract: Australian education policies advocate equal opportunities and nondiscrimination through legislation that people with disabilities willing to attend 'mainstream' schools must be accommodated for. In this paper, people with mobility disabilities talk about their high school experiences in New South Wales, Australia. We are particularly interested in how these men and women talk about the affirmation of bodily differences within various high school spaces. Adopting narrative analysis and a feminist approach we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Another study in Australia on young people with physical disabilities revealed that having both friends and an accessible territory in which to hang out together at school, was important in building both social and spatial connections (De Vet, Waitt, & Gorman-Murray, 2012). In order for learners with intellectual disabilities to interact socially, it is important to develop their communication skills.…”
Section: Teachers Approaches 1 Introductionmentioning
confidence: 99%
“…Another study in Australia on young people with physical disabilities revealed that having both friends and an accessible territory in which to hang out together at school, was important in building both social and spatial connections (De Vet, Waitt, & Gorman-Murray, 2012). In order for learners with intellectual disabilities to interact socially, it is important to develop their communication skills.…”
Section: Teachers Approaches 1 Introductionmentioning
confidence: 99%